Long-term neuropsychological and behavioral outcome of mild and moderate hypoxic ischemic encephalopathy. (February 2022) - Halpin, Stephen; McCusker, Chris; Fogarty, Leanna; White, Jennie; Cavalière, Emilie; Boylan, Geraldine; Murray, Deirdre
Abstract: Background: Outcomes for infants who survive mild-moderate hypoxic ischemic encephalopathy (HIE) into adolescence is relatively uncharted. Aims: We examined neuropsychological and behavioral outcomes in adolescents with mild and moderate HIE, using both parent and self - informants, and including healthy peers and nearest age siblings as controls. Participants: 23 adolescents with a history of mild-moderate HIE (M age = 14.45 years, SD = 1.03; 14 boys and 9 girls) were recruited from an original cohort of 53. A group of their nearest – age siblings ( n = 13), and healthy peers ( n = 14) were recruited as controls. Outcome measures: A number of neuropsychological sub-tests, taken from the WISC-V.UK, Children's Memory Scale, NEPSY, WIAT-III.UK, Rey Complex Figure Copy Test and British Picture Vocabulary Scale were administered. Behavioral adjustment was assessed using the Strengths and Difficulties Questionnaire and the competence subscales of the Child Behavior Checklist . Results: No differences in neuropsychological and behavioral outcomes were observed between mild and moderate HIE cohorts. Together they had significantly lower scores on tests of attention/executive functioning, verbal reasoning and sensory-motor ability compared to healthy peers, with moderate to large effect sizes. Remedial provision at school was greater in the HIE group. Parents reported elevated levels of peer problems in the HIE group compared to both siblings and healthy peers. Reduced competencies were also observed. Conclusions: We found evidence that both mild and moderate survivors of HIE experience neuropsychological, school and peer relationship problems in adolescence. Highlights: We examined outcomes for mild – moderate HIE, with controls, into adolescence. Mild HIE survivors did not do better than moderates. Specific neuropsychological deficits were observed in comparison to controls. Peer problems and competence deficits were noted. Remedial school input was elevated in comparison to healthy controls and siblings.